2019
DOI: 10.3390/cancers11101405
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine Differentiation of Prostate Cancer—An Intriguing Example of Tumor Evolution at Play

Abstract: Our understanding of neuroendocrine prostate cancer (NEPC) has assumed a new perspective in light of the recent advances in research. Although classical NEPC is rarely seen in the clinic, focal neuroendocrine trans-differentiation of prostate adenocarcinoma occurs in about 30% of advanced prostate cancer (PCa) cases, and represents a therapeutic challenge. Even though our knowledge of the mechanisms that mediate neuroendocrine differentiation (NED) is still evolving, the role of androgen deprivation therapy (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
72
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(81 citation statements)
references
References 216 publications
2
72
0
7
Order By: Relevance
“…It is worthy to note that neuroendocrine differentiation is associated with treatment failure and poor outcome in metastatic prostate cancer [5,7]. Moreover, ADT was shown to be a key driver of the neuroendocrine differentiation of the prostate adenocarcinoma to NEPC [8], and so it is not surprising that the incidence of treatment-induced NEPC is rising because of the widespread use of more potent androgen receptor (AR) pathway inhibitors [9]. These latter tumor types are refractory to hormonal therapies and are thought to represent a resistance driven by cellular lineage plasticity [3].…”
Section: Introductionmentioning
confidence: 99%
“…It is worthy to note that neuroendocrine differentiation is associated with treatment failure and poor outcome in metastatic prostate cancer [5,7]. Moreover, ADT was shown to be a key driver of the neuroendocrine differentiation of the prostate adenocarcinoma to NEPC [8], and so it is not surprising that the incidence of treatment-induced NEPC is rising because of the widespread use of more potent androgen receptor (AR) pathway inhibitors [9]. These latter tumor types are refractory to hormonal therapies and are thought to represent a resistance driven by cellular lineage plasticity [3].…”
Section: Introductionmentioning
confidence: 99%
“…The tumor microenvironment includes blood vessels, stromal cells namely, cancer-associated fibroblasts (CAFs), endothelial cells, neuroendocrine cells and infiltrating immune cells, growth factors and chemokines secreted by either tumor cells or stromal cells and many extracellular matrix proteins such as laminin, fibronectin, and collagen (Yates, 2011). Apart from the dynamic interaction between tumor and stromal cells, physical (elasticity and stiffness) and biochemical properties (protein composition) of the extracellular matrix (ECM), as well as access to nutrients and oxygen also governs the cellular plasticity of the tumor cells (Yates, 2011;Davies et al, 2018;Patel et al, 2019). Among the different stromal cells, CAFs play a critical role in modulating the plasticity of the cancer cells.…”
Section: Cell-extrinsic Factorsmentioning
confidence: 99%
“…NEPC is a highly aggressive subtype of PCa [10] . It has been shown to progress aggressively, metastasizing primarily to the visceral organs, tissues and sometimes to the bone [32] . Histologically, it is characterized by poor differentiation in tumors, coil-like, or organoid shaped cells which appear basophilic with distinct nucleoli [32] .…”
Section: Nepc: Molecular Features and Epigeneticsmentioning
confidence: 99%
“…It has been shown to progress aggressively, metastasizing primarily to the visceral organs, tissues and sometimes to the bone [32] . Histologically, it is characterized by poor differentiation in tumors, coil-like, or organoid shaped cells which appear basophilic with distinct nucleoli [32] . In addition, studies have shown that, patients confirmed with NEPC usually develop visceral metastases, have low PSA levels and have frequent loss of retinoblastoma 1 (Rb1) and tumor suppressor p53 (TP53) genes [10,33,34] .…”
Section: Nepc: Molecular Features and Epigeneticsmentioning
confidence: 99%